Structural and functional traits of Quercus ilex in response to water availability (Environmental and Experimental Botany, 2002)
Water potential and morpho-anatomical parameters were measured, during the course of 1 year, on leaves of Quercus ilex trees growing in two coastal stands in Tuscany (Central Italy) with different conditions of water availability: Colognole (CL, mesic site) and Cala Violina (CV, xeric site). Morpho-anatomical measurements included: general leaf features and sclerophylly indices (surface area, thickness, mass per area and density), leaf moisture indices (water content, relative water content, succulence) and histochemical analysis (detection and localization of cutine and tannins in the leaves and starch reserves in the twigs). During the warmest and driest period (August) pre-dawn water potential (pd ) in Holm-oak leaves reached −2.7 MPa at CV and −0.6 MPa at CL. Leaf surface was lower (−34%) and total leaf thickness (+10%), as well as spongy-palisade parenchyma ratio (+20%) were higher at CV. The sclerophylly parameters (leaf mass per area and leaf tissue density) were higher at CV than at CL (+24% leaf mass per area and +19% leaf tissue density). Among the moisture parameters, water content was higher at CL (+8%) and succulence was higher at CV (+13%). No differences in relative water content were observed between the two sites. All the parameters considered were substantially stable during the study period, with the exception of relative water content at CL, that ﬂuctuated within the year. Histochemical analysis revealed a greater thickness of the upper cuticular layer at CV, whereas there were no differences in tannin distribution and content between the two sites. Differences in starch storage were detected in branchlets: it was abundant in CV but very scarce at CL. The strategies of Quercus ilex to cope with water stress were discussed at morpho-structural level.

Structural and functional traits of Quercus ilex in response to water availability - Bussotti, Filippo; Bettini, Davide; Grossoni, Paolo; Mansuino, Silvia; Nibbi, Renzo; Soda, Costanza; Tani, Corrado (Environmental and Experimental Botany, 2002)
Water potential and morpho-anatomical parameters were measured, during the course of 1 year, on leaves of Quercus ilex trees growing in two coastal stands in Tuscany (Central Italy) with different conditions of water availability: Colognole (CL, mesic site) and Cala Violina (CV, xeric site). Morpho-anatomical measurements included: general leaf features and sclerophylly indices (surface area, thickness, mass per area and density), leaf moisture indices (water content, relative water content, succulence) and histochemical analysis (detection and localization of cutine and tannins in the leaves and starch reserves in the twigs). During the warmest and driest period (August) pre-dawn water potential (pd ) in Holm-oak leaves reached −2.7 MPa at CV and −0.6 MPa at CL. Leaf surface was lower (−34%) and total leaf thickness (+10%), as well as spongy-palisade parenchyma ratio (+20%) were higher at CV. The sclerophylly parameters (leaf mass per area and leaf tissue density) were higher at CV than at CL (+24% leaf mass per area and +19% leaf tissue density). Among the moisture parameters, water content was higher at CL (+8%) and succulence was higher at CV (+13%). No differences in relative water content were observed between the two sites. All the parameters considered were substantially stable during the study period, with the exception of relative water content at CL, that ﬂuctuated within the year. Histochemical analysis revealed a greater thickness of the upper cuticular layer at CV, whereas there were no differences in tannin distribution and content between the two sites. Differences in starch storage were detected in branchlets: it was abundant in CV but very scarce at CL. The strategies of Quercus ilex to cope with water stress were discussed at morpho-structural level.
Keywords: leaf structure; starch; Tannins; water potential